Development and evaluation of a website for surveillance of healthcare-associated urinary tract infections in Australia. Issue 1 (May 2018) - Fasugba, O.; Koerner, J.; Bennett, N.; Burrell, S.; Laguitan, R.; Hoskins, A.; Beckingham, W.; Mitchell, B.G.; Gardner, A.
Summary: Phase II of the Surveillance to Reduce Urinary Tract Infections project piloted a website for point prevalence surveys of healthcare-associated (HAUTI) and catheter-associated urinary tract infection in Australian hospitals and aged care homes. This report describes development and evaluation of the website for online data collection. Evaluation findings from 38 data collectors indicated that most respondents found website registration and web form use easy ( N  = 22; 58% and N  = 16; 43%, respectively). The need for improved computer literacy skills and automated data systems were highlighted. This study demonstrated a novel approach for Australian HAUTI data collection; however, refinements are needed before national roll-out.